ANALISIS KEPUASAN WISATAWAN TERHADAP ATRIBUT WISATA MENGGUNAKAN METODE CSI DAN IPA PADA WISATA PEMANDIAN DI KABUPATEN TAPANULI UTARA - Saula Lestari Tampubolon; Devis Wawan Saputra Simanjuntak; Mariana Simanjuntak (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2019)
The tourism industrial is determined as one of the mainstay sector in improving the economy because of its rapid development. With that growing, need to consistently develop the tourism by the product attributes which is deemed important by consumers and used as basis for purchasing decision. Good management of attributes is one of the most effective ways of attracting consumers and to improve the quality can do by measure visitor satisfaction. North Sumatra is one of the most visited provinces as tourist destination, where North Tapanuli is one of its area which has great potentials to be developed into the mainstay tourism and bathing tourism is the most potentially rated tour. The most popular bathing are the Sipoholon, Tamaro Hot Spring and Air Soda. It is necessary to repair the tourism attributes that include attractions, amenities, accessibility and ansilary that are oriented towards the tourist satisfaction so that the priority is obtained indicators that have impacts on travel efficiency. The methods used in this research are the CSI and IPA methods. The result is obtained that CSI value of 68.89% which belongs to the satisfied category and using IPA method obtained that there are 8 attributes that maintain priority improvement.